The incidence and risk factors related to post-operative dysphagia after anterior cervical spine surgery: a prospective study - Jagdeep Singh; Navpreet Singh; Pranav Gupta; Bansal Kapil (Гений oртопедии)
Introduction Post-surgical dysphagia is one complication particularly common in early postoperative period after Anterior cervical spine surgery (ACSS). However, the pathophysiology of dysphagia after surgery has not been well understood. This study aimed to analyse the frequency and risk factors for developing dysphagia following ACSS and find an effective program to prevent and treat. Materials and methods A prospective observational study was conducted on 50 patients undergoing ACSS from April 2021 to Oct 2022 at the Department of Orthopedics, Guru Gobind Singh Medical College and Hospital, Punjab (India). Patients were in the age group of 27 to 60 years. The indications for cervical surgeries were traumatic, degenerative, infective and neoplastic involving C2 to C7 vertebra with signs of neural compression unresponsive to conservative treatment. Data on patient age, gender, duration of surgery, intraoperative blood loss, segment operated and the number of segments operated were collected. Follow up time was 24 weeks. Results Incidence of dysphagia was 20 % (10/50) within first week which reduced to zero at completion of six months of follow-up. Dysphagia was present in 2 % (1/50) patients in age group 21–40 years and 18 % (9/50) patients in age group of 41–60 years. 14.6 % (6/41) males and 44 % (4/9) of females had dysphagia. Prevalence of dysphagia in patients with one affected segment was 9.5 % (4/42), two segments was 80 % (4/5) and three segments was 50 % (1/2). Mean duration of surgery in patients with post-operative dysphagia was 115 mins. Mean blood loss in patients with post-operative dysphagia was 171.40 mL Mean Et (endotracheal) tube cuff pressure in patients with post-operative dysphagia was 24.70 cm H2O. Within the first week of surgery, there were 10 cases out of which one was mild, six were moderate and three were severe. Conclusion Despite the fact that some inconsistency is there in the literature regarding risk factors it can be safely concluded from our study that incidence of post-operative dysphagia can be reduced by decreasing blood loss during surgery, reducing surgery time and optimizing Endotracheal tube cuff pressure during surgery.